Control de tecla thecla basilides en piña con cinco insecticidas orgánicos en la zona de Santo Domingo - Sanmartín Salazar, Ronald Wilmer (2009)
In the Company Agricultural Civil Society and Commercial (SCAC), located in the parish beautiful Valley km 25 of the Quinindé route - Emeralds, province of Santo Domingo of the Tsachilas. The test of control of Thecla was carried out basilides, with five organic insecticides, using like experimental material commercial cultivating of pineapple MD2. The objectives that considered in this investigation were: To prove the efficiency of five organic insecticides for the control of Thecla basilides, in pineapple; to determine or the insecticides that allow to maintain losses populations of Thecla basilides in the culture and to establish the yield of the different treatments. The work consisted of assessing the damage caused by Thecla basilides to the inflorescencia, crowns and fruit, as well as the fenológicas phases of pineapple were observed to register and to identify the oviposición of the plague and therefore some morphologic parameters of the fruit, in response to the treatments applied with insecticides. One tried on the following organic insecticides: Dipel 2X, Cinna-mix, Phyriplus, Diss-sektor and Oleoplus, including carbaryl like conventional witness and an absolute witness for its respective comparison. The experimental design of blocks was used at random, with seven treatments and four repetitions and evaluated the following variables: Egg presence of key in the brácteas and crowns, number of affected flowers, number of affected fruits, presence of larvae by fruit, external length of the fruit and weight of the fruit to the harvest. According to the results one concluded that: The most efficient treatments for the control of Thecla basilides were: Dipel 2X, Cinna-mix, Phyriplus and carbaryl that was used like conventional witness, presenting/displaying 92% of efficiency. The use of these natural insecticides allowed to reduce in significant form the present possibility of damages on the fruits and natural enemies, therefore also they can be used like substitute of chemistry-synthetic insecticides. Of the costs by hectare of five applications with natural insecticides in form manual, the most expensive treatment constituted Cinna-mix and economic 2X was Dipel.